Effect of spacing and foliar spray of banana Pseudostem based organic liquid nutrients on soil physico-chemical properties under mango-based agroforestry system - PATEL, MEHFUZA; TANDEL, M.B.; PATEL, S.M.; DESAI, M.K.; PATEL, D.P.; AHIR, M.P.; GARDE, Y.A. (Journal of Soil and Water Conservation, 2025)
The investigation was conducted during summer season (Feb – June) of the year 2021 and 2022 in cowpea, var. AVCP – 1 (Anand Vegetable Cowpea). Cowpea was grown as an intercrop under Mango based agroforestry system (MAFS) and in open condition. The trial was framed with eight treatment combinations of two factors which contains two levels of spacing viz., S1: 30 cm x 30 cm and S2: 45 cm x 45 cm and four levels of foliar spray of Novel organic liquid fertilizers viz. F1: Control, F2: Novel @ 1%, F3: Novel prime @ 1% and F4: Novel plus @ 1% with three replications and analyzed as per Randomized Block Design with Factorial Concept (FRBD) and t - test. The same treatments were applied in both growing conditions i.e., under mango-based agroforestry system and in open condition. Physical and chemical properties of soil viz. bulk density, particle density, porosity, soil pH, soil EC, SOC, available N, available P2O5 and available K2O did not show any variation in response to various spacing and foliar spray of novel organic liquid fertilizers. However, significantly higher values of porosity (49.95%), soil pH (8.18), SOC (0.58%), available N, P2O5, and K2O (260.50, 85.21 and 718.38 kg ha-1, respectively) were recorded under mango-based agroforestry system in comparison to open condition.